The Primary Cilium: A Small Yet Mighty Organelle - DeRouen, Mindy C. (2009)
Primary cilia are small, cylindrical membrane protrusions on most vertebrate cell types. Despite an unassuming appearance, this organelle has proven to be a veritable nexus of tightly regulated cell-signal reception between the epithelium and mesenchyme. In this issue, Lehman et al. describe the necessity of Ift88 and intra-flagellar transport for signal reception of the sonic hedgehog pathway in the dermal papilla of developing hair follicles.